A new approach to multiple fault diagnosis: A combination of diagnostic matrices, graphs, algebraic and rule-based models. The case of two-layer models - Ligęza, Antoni; Kościelny, Jan Maciej (Zielona Góra: Uniwersytet Zielonogórski)
The diagnosis of multiple faults is significantly more difficult than singular fault diagnosis. However, in realistic industrial systems the possibility of simultaneous occurrence of multiple faults must be taken into account. This paper investigates some of the limitations of the diagnostic model based on the simple binary diagnostic matrix in the case of multiple faults. Several possible interpretations of the diagnostic matrix with rule-based systems are provided and analyzed.
Keywords: automated diagnosis; diagnostic matrix; diagnostic rules; model-based diagnosis; consistency-based diagnosis